Green Synthesis, Molecular Characterization and Associative Behavior of Some Gemini Surfactants without a Spacer Group - Villa, Carla (Materials (Basel), 2013)
A series of new gemini surfactants without a spacer group, disodium 2,3-dialkyl-1,2,3,4-butanetetracarboxylates, were synthesized in a green chemistry context minimizing the use of organic solvents and applying microwaves (MW) when activation energy was required. Once the desired architecture was confirmed by means of the nuclear magnetic resonance technique ((1)H-NMR, (1)H-(1)H COSY) for all the studied surfactants, the critical micellization concentration was determined by conductance measurements. The diffusion coefficient of micelles formed by the four compounds was characterized using pulsed field gradient (PFG)-NMR. Diffusion coefficients were found to be dependent on the concentration and on the number of carbon atoms in the alkyl chain. The absence of the spacer group, peculiar to this new series of gemini surfactants, may confer relatively low flexibility to the molecules, with potential implications on the interfacial properties, namely on micellization. These gemini surfactants might have interesting applications in the preparation of composite materials, in nanotechnology, in gene transfection and mainly, due to the low CMCs, as new interesting ingredients of cosmetics and toiletries.